From Gender Trouble to Translation Trouble: Feminist Poststructuralist Theory in Translation between Anglo-American and German-Speaking Scientific Culture - Wenzel, Xenia (chronotopos – A Journal of Translation History, 2020)
This paper examines “Gender Trouble” by Judith Butler as an example of the poststructuralist paradigm in feminist theory and its translation into the German-speaking scientific discourse using concepts from both the sociology of scientific knowledge and translation history. First it explores the discursive, societal and historical contexts of the origins of “Gender Trouble” in the U.S. around 1990, when poststructuralist approaches were common in feminist theory, while German-speaking feminist debates were still dominated by second wave feminist thought and thus rather focused on body and matter. Part two describes how the German translation of “Gender Trouble” entered the scientific and feminist discourse in the early 1990s. The discourse, although seeming diametrically opposed to the one in the U.S., was changed sustainably by this new text. The study argues that when a translation enters another scientific culture, two different styles of thoughts and languages clash, which impacts both target and source discourse. With its focus on the historic and societal foundations of science and its translation, this paper contributes to a conceptualization of the translation of science but also argues for a new translation of “Gender Trouble” in the ever-changing field of feminist debate.